Heat preservation and soil moisture conservation PE composite mulching film and preparation method thereof
By combining modified epoxy resin and modified polyethylene, PE composite plastic films with improved durability, ultraviolet resistance and thermal insulation properties were prepared, which solved the problem of poor aging resistance of existing PE plastic films, significantly extended the service life and improved the performance.
Patent Information
- Application Number
- CN202411654229.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The aging resistance of existing PE plastic films is poor, especially in areas with strong ultraviolet light, which is prone to photoaging and mechanical aging, which affects the use value.
PE composite plastic film is prepared by melt extrusion, casting and other processes. Modified epoxy resins form a crosslinking network by blending with modified polyurethane to improve toughness and durability; modified polyethylene enhances UV and thermal insulation properties by adding anti-ultraviolet derivatives and infrared absorbers.
It significantly improves the mechanical properties, UV resistance and moisture retention properties of PE composite mulch, extends the service life, and reduces the aging speed under ultraviolet light, and improves the thermal insulation effect.
Smart Images

Figure BDA0005141741820000141 
Figure BDA0005141741820000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PE films, in particular to a heat-insulating and moisture-retaining PE composite ground film and a preparation method thereof. Background Art
[0002] PE (polyethylene) mulch is generally transparent or black, with a thickness of 10 to 30 μm. It is used for ground covering and has good heat preservation and moisture retention properties. It also has the functions of preventing diseases and pests, drought and waterlogging, and improving near-ground light and heat conditions. It is highly targeted and applicable to my country's arid, barren, rainless and short frost-free areas. It has been popularized and used in 31 provinces, cities and autonomous regions across the country, and is deeply welcomed by farmers.
[0003] Chinese patent CN109677070A discloses a PE ground film, which provides a PE ground film with high sunlight transmittance and good warming effect.
[0004] However, ordinary PE mulch has poor aging resistance and is less useful in areas with strong ultraviolet radiation. After being exposed to ultraviolet radiation, it reacts with air pollutants and pesticides to cause light aging. Mechanical tension can also cause the joints to break, causing mechanical aging and crushing, and adhere to the surface of crops, polluting the environment. In order to enhance the anti-ultraviolet ability and heat preservation and moisture retention ability of PE mulch, we propose a heat preservation and moisture retention PE composite mulch and its preparation method. Summary of the invention
[0005] The object of the present invention is to provide a heat-insulating and moisture-retaining PE composite mulch film and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a heat-insulating and moisture-retaining PE composite ground film, comprising the following mass components: 20 to 40 parts of modified epoxy resin and 60 to 80 parts of modified polyethylene.
[0007] Furthermore, the modified epoxy resin is obtained by grafting epoxy resin with modified polyurethane.
[0008] Furthermore, the modified polyethylene is prepared by mixing an anti-ultraviolet derivative, polyethylene and an infrared absorber.
[0009] A method for preparing a heat-insulating and moisture-retaining PE composite mulch film comprises the following steps:
[0010] The modified epoxy resin and the modified polyethylene are mixed, melt-extruded, cast into a film, cooled and shaped to form a PE composite ground film.
[0011] Furthermore, the mass ratio of modified epoxy resin to modified polyethylene is (20-40):(60-80).
[0012] Furthermore, the process conditions of melt extrusion are: temperature 190-210° C., rotation speed 40-50 r / min.
[0013] Furthermore, the thickness of the PE composite mulch film is 15 μm.
[0014] Furthermore, the modified epoxy resin is prepared by the following process:
[0015] The modified polyurethane, epoxy resin and dibutyltin dilaurate are mixed, and the reaction is carried out at 65-75°C for 1-2 hours under the protection of nitrogen atmosphere. After the reaction, vacuum degassing is carried out for 10-20 minutes to obtain the modified epoxy resin.
[0016] Furthermore, the mass ratio of modified polyurethane, epoxy resin and dibutyltin dilaurate is (5-7):1:(0.2-0.4).
[0017] Furthermore, the epoxy resin is E51, epoxy equivalent: 184-195 g / mol, viscosity: 10000-16000 mPa·s, sourced from Jiangyin Wanqian Chemicals Co., Ltd.;
[0018] Dibutyltin dilaurate: CAS number is 77-58-7, sourced from Jilin Huaxin Chemical Co., Ltd.
[0019] Further, the modified polyurethane is obtained by mixing CaCO3, talcum powder and polyurethane, and the specific process is as follows:
[0020] CaCO3, talcum powder and polyurethane are mixed, melt-extruded, cooled and pelletized to obtain modified polyurethane.
[0021] Furthermore, the mass ratio of CaCO3, talc and polyurethane is (0.5-1):(1-3):(5-7).
[0022] Furthermore, the process conditions of melt extrusion are: temperature 165-195° C., rotation speed 50-70 r / min.
[0023] Further, CaCO3: CAS number is 471-34-1, which comes from Quanzhou Xufeng Powder Raw Material Co., Ltd.;
[0024] Polyurethane: purity 99%, sourced from Dongguan Yuehaoxuan Plastic Co., Ltd.
[0025] Furthermore, the talcum powder is modified, and the specific process is as follows:
[0026] The talc powder and maleic anhydride are mixed at high speed, and then paraffin is added and mixed at high speed again to obtain modified talc powder.
[0027] Furthermore, the mass ratio of talc, maleic anhydride and paraffin is 1:(0.3-0.5):(0.1-0.5).
[0028] Furthermore, the process conditions for high-speed mixing are: rotation speed 2000-2500 r / min, time 5-10 min, temperature 70-80°C.
[0029] Furthermore, talcum powder is preheated to 50-60°C before use.
[0030] Further, talcum powder: CAS number 14807-96-6, particle size 1250 mesh, sourced from Jinan Tianqiao Xinfu Chemical Products Business Center;
[0031] Maleic anhydride: CAS number is 108-31-6, sourced from Jinan Century Tongda Chemical Co., Ltd.
[0032] Paraffin: CAS number is 8002-74-2, purity is 99%, and it comes from Jingxian Longyuan Chemical Co., Ltd.
[0033] In the above technical scheme, modified polyurethane and epoxy resin are melt-blended to form a cross-linked interpenetrating network structure, which improves the toughness, durability and crack resistance of the epoxy resin, and at the same time improves the water stability of the polyurethane, and improves the mechanical properties and service life of the composite mulch. The addition of CaCO3 and talcum powder makes the chemical properties of the polyurethane more stable, improves the dispersibility of the polyurethane in the epoxy resin, and also reduces the water vapor permeability, thereby enhancing the moisture retention performance of the composite mulch. However, the surface energy of talcum powder is relatively high, and its physical and chemical properties are quite different from those of the polymer. Direct addition is likely to lead to a decrease in the performance of the material. Therefore, the talcum powder is modified with an organic acid and then coated with paraffin for the second time, which improves the compatibility of talcum powder with polyurethane and improves the mechanical properties of the composite mulch to a certain extent.
[0034] Furthermore, the modified polyethylene is prepared by the following process:
[0035] The anti-ultraviolet derivative, polyethylene and infrared absorber are mixed, melt-extruded, dried and pelletized to obtain modified polyethylene.
[0036] Furthermore, the mass ratio of the anti-ultraviolet derivative, polyethylene and infrared absorber is (3-5):100:(1-3).
[0037] Furthermore, the process conditions of melt extrusion are: temperature 160-170° C., rotation speed 100-130 r / min.
[0038] Furthermore, the drying process conditions are: temperature 60-80° C., time 6-12 h.
[0039] Further, polyethylene: CAS number is 9002-88-4, which is sourced from Henan Ouke Plastic Industry Co., Ltd.;
[0040] Infrared absorber: The brand is HSYP-01, which comes from Qingdao Jidejia New Material Technology Co., Ltd.
[0041] Furthermore, the anti-ultraviolet derivative is obtained by grafting the ultraviolet absorber with methyl hydrogen polysiloxane, and the specific process is as follows:
[0042] The ultraviolet absorber, methyl hydrogen polysiloxane and toluene are mixed, heated to 80-100° C., a platinum catalyst is added to react for 4-6 hours, low boiling substances are removed under reduced pressure, cooled, washed with a methanol-acetone mixed solution for 3-5 times, and vacuum dried to obtain an anti-ultraviolet derivative.
[0043] Furthermore, the mass ratio of the ultraviolet absorber, methyl hydrogen polysiloxane, toluene and platinum catalyst is 10:(1-3):(3-5):(0.08-0.1).
[0044] Furthermore, the methanol-acetone mixed solution was homemade in the laboratory, and the volume ratio of methanol to acetone was 5:1.
[0045] Furthermore, the process conditions of vacuum drying are: temperature 78-82° C., time 20-24 h.
[0046] Further, methyl hydrogen polysiloxane: CAS number 63148-57-2, hydrogen content 0.045%, sourced from Shandong Luderui New Materials Co., Ltd.;
[0047] Toluene: CAS number is 108-88-3, from Merck reagent;
[0048] Platinum catalyst: brand S-201, from Shanghai Neutron Star Chemical Technology Co., Ltd.;
[0049] Methanol: CAS number is 67-56-1, from Jinan Ruishan Chemical Co., Ltd.
[0050] Acetone: CAS number is 67-64-1, from Merck Reagent.
[0051] Furthermore, the ultraviolet absorber is prepared by the following process:
[0052] 2,4-dihydroxybenzophenone and N-hydroxymethyl acrylamide-ethanol solution are mixed, and the temperature is raised to 50-70° C. under the protection of nitrogen atmosphere, and the mixture is reacted for 4-6 hours to obtain an ultraviolet absorber.
[0053] Furthermore, the N-hydroxymethyl acrylamide-ethanol solution was homemade in the laboratory, wherein the ethanol ratio was 7 g / mL.
[0054] Furthermore, the mass ratio of 2,4-dihydroxybenzophenone to N-hydroxymethyl acrylamide-ethanol solution is 1:(1-3).
[0055] Further, 2,4-dihydroxybenzophenone: CAS number 623-05-2, sourced from Shanghai Yuanye Biotechnology Co., Ltd.;
[0056] N-hydroxymethyl acrylamide: CAS number is 924-42-5, from Shanghai Darui Fine Chemicals Co., Ltd.;
[0057] Ethanol is anhydrous ethanol with CAS number 64-17-5, which comes from Shanghai Xiangheyi Chemical Technology Co., Ltd.
[0058] In the above technical scheme, 2,4-dihydroxybenzophenone and N-hydroxymethyl acrylamide are mixed, and an acrylamide group is introduced into 2,4-dihydroxybenzophenone. The generated ultraviolet absorber has high anti-ultraviolet ability, and then it is grafted with methyl hydrogen polysiloxane, and polyorganosiloxane is introduced into the side chain of the ultraviolet absorber, which has a good absorption effect on ultraviolet light, further increasing the anti-ultraviolet performance of the composite mulch and reducing the aging rate; the addition of infrared absorber can absorb infrared heat radiation dissipated from the surface, which can effectively prevent heat loss, thereby achieving a better thermal insulation effect.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] 1. The stability of polyurethane is improved by modifying polyurethane with CaCO3 and talcum powder, and its dispersibility in epoxy resin is improved. At the same time, the water vapor permeability is reduced, and the moisture retention performance of the composite mulch is enhanced. The modified polyurethane and epoxy resin are melt-blended to improve the toughness, durability and crack resistance of the epoxy resin, and at the same time improve the water stability of polyurethane, and improve the mechanical properties and service life of the composite mulch. Talc is modified with organic acid and then coated with paraffin for the second time, which improves the compatibility of talc and polyurethane, and improves the mechanical properties of the composite film to a certain extent.
[0061] 2. By mixing 2,4-dihydroxybenzophenone and N-hydroxymethyl acrylamide, an ultraviolet absorber containing acrylamide groups was prepared, which improved its anti-ultraviolet ability. It was then grafted with methyl hydrogen polysiloxane and polyorganosiloxane was introduced on the side chain of the ultraviolet absorber, which has a good absorption effect on ultraviolet light, further increasing the anti-ultraviolet performance of the composite mulch and reducing the aging rate. The addition of infrared absorbers can absorb infrared heat radiation dissipated from the surface, which can effectively prevent heat loss and achieve better thermal insulation effect. DETAILED DESCRIPTION
[0062] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] In the following specific implementations,
[0064] The epoxy resin is E51, epoxy equivalent: 184-195 g / mol, viscosity: 10000-16000 mPa·s, from Jiangyin Wanqian Chemicals Co., Ltd.
[0065] Dibutyltin dilaurate: CAS number is 77-58-7, sourced from Jilin Huaxin Chemical Co., Ltd.;
[0066] CaCO3: CAS number is 471-34-1, from Quanzhou Xufeng Powder Raw Materials Co., Ltd.
[0067] Polyurethane: purity 99%, sourced from Dongguan Yuehaoxuan Plastic Co., Ltd.;
[0068] Talc: CAS number is 14807-96-6, particle size is 1250 mesh, sourced from Jinan Tianqiao Xinfu Chemical Products Business Center;
[0069] Maleic anhydride: CAS number is 108-31-6, sourced from Jinan Century Tongda Chemical Co., Ltd.
[0070] Paraffin: CAS number is 8002-74-2, purity is 99%, from Jingxian Longyuan Chemical Co., Ltd.;
[0071] Polyethylene: CAS number is 9002-88-4, sourced from Henan Ouke Plastic Industry Co., Ltd.
[0072] Infrared absorber: brand name HSYP-01, from Qingdao Jiedejia New Material Technology Co., Ltd.;
[0073] Methyl hydrogen polysiloxane: CAS number is 63148-57-2, hydrogen content is 0.045%, from Shandong Luderui New Materials Co., Ltd.
[0074] Toluene: CAS number is 108-88-3, from Merck reagent;
[0075] Platinum catalyst: brand S-201, from Shanghai Neutron Star Chemical Technology Co., Ltd.;
[0076] Methanol: CAS number is 67-56-1, from Jinan Ruishan Chemical Co., Ltd.
[0077] Acetone: CAS number is 67-64-1, from Merck reagent;
[0078] 2,4-Dihydroxybenzophenone: CAS number is 623-05-2, from Shanghai Yuanye Biotechnology Co., Ltd.;
[0079] N-hydroxymethyl acrylamide: CAS number is 924-42-5, from Shanghai Darui Fine Chemicals Co., Ltd.;
[0080] Ethanol is anhydrous ethanol with CAS number 64-17-5, which comes from Shanghai Xiangheyi Chemical Technology Co., Ltd.
[0081] The thickness of the PE composite mulch film is 15 μm.
[0082] Embodiment 1: A method for preparing a heat-insulating and moisture-retaining PE composite mulch film, comprising the following processes:
[0083] Step (1) Preparation of modified epoxy resin:
[0084] The talc powder and maleic anhydride are mixed at high speed, and then paraffin is added and mixed at high speed again to obtain modified talc powder; the mass ratio of talc powder, maleic anhydride and paraffin is 1:0.3:0.1; the process conditions of high-speed mixing are: speed 2000r / min, time 5min, temperature 70℃; the talc powder is preheated to 50℃ before use;
[0085] CaCO3, modified talcum powder and polyurethane were mixed in a mass ratio of 0.5:1:5, melt-extruded, cooled and pelletized to obtain modified polyurethane; the process conditions of melt-extrusion were: temperature 165°C, speed 50r / min;
[0086] The modified polyurethane, epoxy resin and dibutyltin dilaurate were mixed in a mass ratio of 5:1:0.2, and reacted at 65°C for 1 hour under the protection of nitrogen atmosphere. After the reaction, vacuum degassing was performed for 10 minutes to obtain the modified epoxy resin.
[0087] Step (2) Preparation of modified polyethylene:
[0088] 2,4-dihydroxybenzophenone and N-hydroxymethyl acrylamide-ethanol solution were mixed in a mass ratio of 1:1, and the temperature was raised to 50°C for reaction for 4 hours under the protection of nitrogen atmosphere to obtain a UV absorber; the proportion of ethanol in the N-hydroxymethyl acrylamide-ethanol solution was 7g / mL;
[0089] The ultraviolet absorber, methyl hydrogen polysiloxane and toluene were mixed, heated to 80°C, a platinum catalyst was added to react for 4 hours, low boiling points were removed under reduced pressure, cooled, washed 3 times with a methanol-acetone mixed solution, and vacuum dried to obtain an anti-ultraviolet derivative; the mass ratio of the ultraviolet absorber, methyl hydrogen polysiloxane, toluene and platinum catalyst was 10:1:3:0.08; the volume ratio of methanol to acetone in the methanol-acetone mixed solution was 5:1; the process conditions for vacuum drying were: temperature 78°C, time 20 hours;
[0090] The anti-ultraviolet derivative, polyethylene and infrared absorber are mixed in a mass ratio of 3:100:1, melt-extruded, dried and pelletized to obtain modified polyethylene; the process conditions of melt-extrusion are: temperature 160°C, speed 100r / min; the process conditions of drying are: temperature 60°C, time 6h;
[0091] Step (3) Preparation of PE composite mulch film:
[0092] The modified epoxy resin and the modified polyethylene are mixed in a mass ratio of 20:80, melt-extruded, cast into a film, cooled and shaped to form a PE composite mulch film; the process conditions of the melt-extrusion are: temperature 190°C, rotation speed 40r / min; the thickness of the PE composite mulch film is 15μm.
[0093] Embodiment 2: A method for preparing a heat-insulating and moisture-retaining PE composite mulch film, comprising the following processes:
[0094] Step (1) Preparation of modified epoxy resin:
[0095] The talc powder and maleic anhydride are mixed at high speed, and then paraffin is added and mixed at high speed again to obtain modified talc powder; the mass ratio of talc powder, maleic anhydride and paraffin is 1:0.4:0.3; the process conditions of high-speed mixing are: speed 2300r / min, time 7min, temperature 75℃; the talc powder is preheated to 55℃ before use;
[0096] CaCO3, modified talc and polyurethane were mixed in a mass ratio of 0.7:2:6, melt extruded, cooled and pelletized to obtain modified polyurethane; the process conditions of melt extrusion were: temperature 180°C, speed 60r / min;
[0097] The modified polyurethane, epoxy resin and dibutyltin dilaurate were mixed in a mass ratio of 6:1:0.3, and reacted at 70°C for 1.5 hours under the protection of nitrogen atmosphere. After the reaction, vacuum degassing was performed for 15 minutes to obtain the modified epoxy resin.
[0098] Step (2) Preparation of modified polyethylene:
[0099] 2,4-dihydroxybenzophenone and N-hydroxymethyl acrylamide-ethanol solution were mixed in a mass ratio of 1:2, and the temperature was raised to 60°C for reaction for 5 hours under the protection of nitrogen atmosphere to obtain a UV absorber; the proportion of ethanol in the N-hydroxymethyl acrylamide-ethanol solution was 7g / mL;
[0100] The ultraviolet absorber, methyl hydrogen polysiloxane and toluene were mixed, heated to 90°C, a platinum catalyst was added to react for 5 hours, low boiling points were removed under reduced pressure, cooled, washed 4 times with a methanol-acetone mixed solution, and vacuum dried to obtain an anti-ultraviolet derivative; the mass ratio of the ultraviolet absorber, methyl hydrogen polysiloxane, toluene and platinum catalyst was 10:2:4:0.09; the volume ratio of methanol to acetone in the methanol-acetone mixed solution was 5:1; the process conditions for vacuum drying were: temperature 80°C, time 22 hours;
[0101] The anti-ultraviolet derivative, polyethylene and infrared absorber are mixed in a mass ratio of 4:100:2, melt-extruded, dried and pelletized to obtain modified polyethylene; the process conditions of melt-extrusion are: temperature 165°C, speed 115r / min; the process conditions of drying are: temperature 70°C, time 9h;
[0102] Step (3) Preparation of PE composite mulch film:
[0103] The modified epoxy resin and the modified polyethylene are mixed in a mass ratio of 30:70, melt-extruded, cast into a film, cooled and shaped to form a PE composite mulch film; the process conditions of the melt-extrusion are: temperature 200°C, rotation speed 45r / min; the thickness of the PE composite mulch film is 15μm.
[0104] Embodiment 3: A method for preparing a heat-insulating and moisture-retaining PE composite mulch film, comprising the following processes:
[0105] Step (1) Preparation of modified epoxy resin:
[0106] The talc powder and maleic anhydride are mixed at high speed, and then paraffin is added and mixed at high speed again to obtain modified talc powder; the mass ratio of talc powder, maleic anhydride and paraffin is 1:0.5:0.5; the process conditions of high-speed mixing are: speed 2500r / min, time 10min, temperature 80℃; the talc powder is preheated to 60℃ before use;
[0107] CaCO3, modified talc and polyurethane were mixed in a mass ratio of 1:3:7, melt extruded, cooled and pelletized to obtain modified polyurethane; the process conditions of melt extrusion were: temperature 195°C, speed 70r / min;
[0108] The modified polyurethane, epoxy resin and dibutyltin dilaurate were mixed in a mass ratio of 7:1:0.4, and reacted at 75°C for 2 hours under the protection of nitrogen atmosphere. After the reaction, vacuum degassing was performed for 20 minutes to obtain the modified epoxy resin.
[0109] Step (2) Preparation of modified polyethylene:
[0110] 2,4-dihydroxybenzophenone and N-hydroxymethyl acrylamide-ethanol solution were mixed in a mass ratio of 1:3, and the temperature was raised to 70°C for reaction for 6 hours under the protection of nitrogen atmosphere to obtain a UV absorber; the proportion of ethanol in the N-hydroxymethyl acrylamide-ethanol solution was 7g / mL;
[0111] The ultraviolet absorber, methyl hydrogen polysiloxane and toluene are mixed, heated to 100°C, a platinum catalyst is added to react for 6 hours, low boiling points are removed under reduced pressure, cooled, washed 5 times with a methanol-acetone mixed solution, and vacuum dried to obtain an anti-ultraviolet derivative; the mass ratio of the ultraviolet absorber, methyl hydrogen polysiloxane, toluene and platinum catalyst is 10:3:5:0.1; the volume ratio of methanol to acetone in the methanol-acetone mixed solution is 5:1; the process conditions of vacuum drying are: temperature 82°C, time 24 hours;
[0112] The anti-ultraviolet derivative, polyethylene and infrared absorber are mixed in a mass ratio of 5:100:3, melt-extruded, dried and pelletized to obtain modified polyethylene; the process conditions of melt-extrusion are: temperature 170°C, speed 130r / min; the process conditions of drying are: temperature 80°C, time 12h;
[0113] Step (3) Preparation of PE composite mulch film:
[0114] The modified epoxy resin and the modified polyethylene are mixed in a mass ratio of 40:80, melt-extruded, cast into a film, cooled and shaped to form a PE composite mulch film; the process conditions of the melt-extrusion are: temperature 210°C, rotation speed 50r / min; the thickness of the PE composite mulch film is 15μm.
[0115] Comparative Example 1: Taking Example 1 as a comparison, without modifying the epoxy resin, a method for preparing a heat-insulating and moisture-retaining PE composite mulch film includes the following processes:
[0116] Step (1) Preparation of modified polyethylene: the same as in Example 1;
[0117] Step (2) Preparation of PE composite mulch film:
[0118] Epoxy resin and modified polyethylene are mixed in a mass ratio of 20:80, melt-extruded, cast into a film, cooled and shaped to form a PE composite mulch film; the process conditions for melt extrusion are: temperature 190°C, rotation speed 40r / min; the thickness of the PE composite mulch film is 15μm.
[0119] Comparative Example 2: Compared with Example 1, no infrared absorber is added to the modified polyethylene, and a method for preparing a heat-insulating and moisture-retaining PE composite mulch film includes the following processes:
[0120] Step (1) Preparation of modified epoxy resin: the same as in Example 1;
[0121] Step (2) Preparation of modified polyethylene:
[0122] 2,4-dihydroxybenzophenone and N-hydroxymethyl acrylamide-ethanol solution were mixed in a mass ratio of 1:1, and the temperature was raised to 50°C for reaction for 4 hours under the protection of nitrogen atmosphere to obtain a UV absorber; the proportion of ethanol in the N-hydroxymethyl acrylamide-ethanol solution was 7g / mL;
[0123] The ultraviolet absorber, methyl hydrogen polysiloxane and toluene were mixed, heated to 80°C, a platinum catalyst was added to react for 4 hours, low boiling points were removed under reduced pressure, cooled, washed 3 times with a methanol-acetone mixed solution, and vacuum dried to obtain an anti-ultraviolet derivative; the mass ratio of the ultraviolet absorber, methyl hydrogen polysiloxane, toluene and platinum catalyst was 10:1:3:0.08; the volume ratio of methanol to acetone in the methanol-acetone mixed solution was 5:1; the process conditions for vacuum drying were: temperature 78°C, time 20 hours;
[0124] The anti-ultraviolet derivative and polyethylene are mixed in a mass ratio of 3:100, melt-extruded, dried and pelletized to obtain modified polyethylene; the process conditions of melt-extrusion are: temperature 160°C, rotation speed 100r / min; the process conditions of drying are: temperature 60°C, time 6h;
[0125] Step (3) Preparation of PE composite mulch: Same as Example 1.
[0126] Comparative Example 3: Compared with Example 1, no anti-ultraviolet derivative is added to the modified polyethylene, and a method for preparing a heat-insulating and moisture-retaining PE composite mulch film includes the following processes:
[0127] Step (1) Preparation of modified epoxy resin: the same as in Example 1;
[0128] Step (2) Preparation of modified polyethylene:
[0129] The polyethylene and the infrared absorber are mixed in a mass ratio of 100:1, melt-extruded, dried and pelletized to obtain the modified polyethylene; the process conditions of melt-extrusion are: temperature 160°C, speed 100r / min; the process conditions of drying are: temperature 60°C, time 6h;
[0130] Step (3) Preparation of PE composite mulch: Same as Example 1.
[0131] Comparative Example 4: Compared with Example 1, no modified talc is added to the modified polyurethane, and a method for preparing a heat-insulating and moisture-retaining PE composite mulch film includes the following processes:
[0132] Step (1) Preparation of modified epoxy resin:
[0133] CaCO3 and polyurethane were mixed in a mass ratio of 0.5:5, melt-extruded, cooled and pelletized to obtain modified polyurethane; the process conditions of melt-extrusion were: temperature 165°C, speed 50r / min;
[0134] The modified polyurethane, epoxy resin and dibutyltin dilaurate were mixed in a mass ratio of 5:1:0.2, and reacted at 65°C for 1 hour under the protection of nitrogen atmosphere. After the reaction, vacuum degassing was performed for 10 minutes to obtain the modified epoxy resin.
[0135] Step (2) Preparation of modified polyethylene: same as in Example 1;
[0136] Step (3) Preparation of PE composite mulch: Same as Example 1.
[0137] experiment:
[0138] The composite mulch films obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were prepared into samples, and their properties were tested respectively:
[0139] Tensile performance test: GB / T 528 was used as the reference standard to test the tensile performance at a tensile rate of 90 mm / min.
[0140] Thermal insulation performance test: The thermal conductivity of the sample is tested using a thermal constant analyzer as an indicator of thermal insulation capacity;
[0141] Anti-ultraviolet performance test: tested according to GB / T16422.3-2014 for 360 hours;
[0142] Moisture retention performance test: Determined according to GB / T 1037-2021 "Determination of water vapor transmission properties of plastic films and sheets-Cup weight gain and weight loss method";
[0143]
[0144] Table 1 Performance test data before UV aging
[0145]
[0146] Table 2 Performance test data after UV aging
[0147] According to the data in the above table, we can clearly draw the following conclusions:
[0148] The composite mulch obtained in Examples 1-3 is compared with the composite mulch obtained in Comparative Examples 1-4. The test results show that:
[0149] Compared with Comparative Example 1, the composite mulch films obtained in Examples 1-4 have better tensile strength, UV resistance, thermal insulation and moisture retention properties.
[0150] Compared with Example 1, Comparative Example 1 does not modify the epoxy resin, and cannot form a cross-linked interpenetrating network structure, and the mechanical properties of the composite mulch film decrease significantly; Comparative Example 2 does not add an infrared absorber, and cannot absorb the infrared heat radiation dissipated from the surface, so the heat dissipation is fast and the thermal insulation effect decreases; Comparative Example 3 does not add anti-ultraviolet derivatives, and the protective effect of the composite mulch film against ultraviolet rays is weak, resulting in a significant decrease in the tensile properties of the composite mulch film after ultraviolet aging; Comparative Example 4 does not add modified talcum powder, and the thermal insulation and moisture retention effects of the composite mulch film are significantly reduced. It can be seen that the preparation process of the composite mulch film and the setting of the components used in the present application can promote the comprehensive improvement of its mechanical properties, thermal insulation and moisture retention properties, and anti-ultraviolet properties.
[0151] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A heat-insulating and moisture-retaining PE composite mulch film, characterized in that: It comprises the following components by mass: 20 to 40 parts of modified epoxy resin and 60 to 80 parts of modified polyethylene; The modified epoxy resin is obtained by grafting epoxy resin with modified polyurethane.
2. The heat-insulating and moisture-retaining PE composite mulch film according to claim 1, characterized in that: The modified polyethylene is prepared by mixing an anti-ultraviolet derivative, polyethylene and an infrared absorber.
3. The heat-insulating and moisture-retaining PE composite mulch film according to claim 1, characterized in that: The modified polyurethane is prepared by mixing CaCO3, talcum powder and polyurethane.
4. A method for preparing a heat-insulating and moisture-retaining PE composite mulch film, characterized in that: Including the following processes: The modified epoxy resin and the modified polyethylene are mixed, melt-extruded, cast into a film, cooled and shaped to form a PE composite ground film.
5. The method for preparing a heat-insulating and moisture-retaining PE composite mulch film according to claim 4, characterized in that: The modified epoxy resin is prepared by the following process: The modified polyurethane, epoxy resin and dibutyltin dilaurate are mixed, and the reaction is carried out at 65-75°C for 1-2 hours under the protection of nitrogen atmosphere. After the reaction, vacuum degassing is carried out for 10-20 minutes to obtain the modified epoxy resin.
6. The method for preparing a heat-insulating and moisture-retaining PE composite mulch film according to claim 5, characterized in that: The modified polyurethane is prepared by the following process: CaCO3, talcum powder and polyurethane are mixed, melt-extruded, cooled and pelletized to obtain modified polyurethane.
7. The method for preparing a heat-insulating and moisture-retaining PE composite mulch film according to claim 4, characterized in that: The modified polyethylene is prepared by the following process: The anti-ultraviolet derivative, polyethylene and infrared absorber are mixed, melt-extruded, dried and pelletized to obtain modified polyethylene.
8. The method for preparing a heat-insulating and moisture-retaining PE composite mulch film according to claim 7, characterized in that: The anti-ultraviolet derivative is prepared by the following process: The ultraviolet absorber, methyl hydrogen polysiloxane and toluene are mixed, heated to 80-100° C., a platinum catalyst is added to react for 4-6 hours, low boiling substances are removed under reduced pressure, cooled, washed with a methanol-acetone mixed solution for 3-5 times, and vacuum dried to obtain an anti-ultraviolet derivative.
9. The method for preparing a heat-insulating and moisture-retaining PE composite mulch film according to claim 6, characterized in that: The talcum powder is modified, and the specific process is as follows: The talc powder and maleic anhydride are mixed at high speed, and then paraffin is added and mixed at high speed again to obtain modified talc powder.
10. The method for preparing a heat-insulating and moisture-retaining PE composite mulch film according to claim 8, characterized in that: The ultraviolet absorber is prepared by the following process: 2,4-dihydroxybenzophenone and N-hydroxymethyl acrylamide-ethanol solution are mixed, and the temperature is raised to 50-70° C. under the protection of nitrogen atmosphere, and the mixture is reacted for 4-6 hours to obtain an ultraviolet absorber.
Citation Information
Patent Citations
Waterborne polyurethane-epoxy interpenetrating network superfine cement compound grouting material, preparation method thereof and application of grouting material
CN107721309A
Novel anti-ultraviolet finishing agent and synthesis method thereof
CN109957967A
Polymerized ultraviolet absorbent, acrylic resin, and preparation method of modified epoxy coating
CN111646918A
Cationic high-molecular ultraviolet absorber
JP1994073367A
Cited By
High-strength recoverable high-heat-preservation mulching film and preparation method thereof
CN120590701A
Recycled aluminum-plastic panel master batch prepared by recycling waste mulching film and preparation method of recycled aluminum-plastic panel master batch
CN122445131A